Normative and informational confidence matching - Friedemann, M; Bang, D; Yeung, N (American Psychological Association, 2024)
When performing tasks in a social context, individuals tend to report confidence judgments that increasingly align with those of others over time. However, the mechanisms underlying this phenomenon, termed confidence matching, are not fully understood. This study explores two potential drivers of confidence matching behaviour: informational factors that cause individuals to genuinely recalibrate their private sense of confidence based on their partner’s confidence; and normative factors that lead individuals to adapt the way in which they publicly express their confidence, without changing their private assessment of their own performance. To examine these influences, we conducted two experiments examining the effects of both informational and normative factors on private and public confidence. The results demonstrate that both factors can lead to confidence matching. In a setting devoid of feedback, participants matched their confidence reports with their partner’s and modified their information seeking behaviour — a proxy for private confidence — accordingly, pointing towards the role of informational factors. Conversely, in a scenario in which feedback was readily available and a joint decision-making rule was enforced, participants aligned their confidence reports with their partner’s but did not adjust their information seeking behaviour, hinting at normative factors influencing the public display of confidence matching. These findings highlight the flexibility and contextsensitivity of confidence, thereby underscoring the importance of factoring in social contexts and the adaptive nature of confidence when studying metacognitive processes.